Areas of maximum intensity of avalanche formation in the Greater Caucasus associated with large anomalies of temperature and humidity regime - A. D. Oleynikov (Лëд и снег, 2024)
Дано обоснование географических границ районов, которые при крупномасштабных гидрометеорологических аномалиях выделяются по интенсивности лавинопроявления среди других районов Кавказа имогут быть отнесены к «эпицентрам» лавинной деятельности.Перенести в английский вариант   The purpose of this paper is to substantiate the geographical boundaries of areas which are distinguished in the Greater Caucasus by the intensity of avalanche formation at the large-scale hydrometeorological anomalies and can be classified as “epicentres” of the avalanche activity.   For the period of snow avalanche observations in the Caucasus in the 20th century, the Nature did twice demonstrate “experiments” in the winters of 1975/76 and 1986/87, during which especially intensive releases of avalanches occurred in the same areas of the southern macro-slope of the Central Caucasus. This work is an effort to answerthe question ‒ why the main impacts of the snow disasters occurred within the boundaries of the same territories. The results of the analysis show that the highest intensity of avalanche activity is observedin those areas where three factors of avalanche formation are simultaneously realized: a big number of large avalanche catchments, including ancient glacial cirque zones (corries); high snowiness; types ofsnow favourable for the mass releases of especially strong avalanches. In the Caucasus, these criteria are met by the usually identified watershed zone of the Main Caucasus Range and, as the analysis showed,the territory of mountainous Georgia in the Inguri River basin (with tributaries of the Nenskra, Nakra, Mestia-Chala, Dolra, Mulkhura rivers), as well as the upper reaches of the river Kodori (Abkhazia). According to the USSR Glacier Inventory (1986), up to 80% of the corrie relief forms of the southern macro-slope of the Caucasus are concentrated in the basins of the Inguri and Kodori rivers, many of which are centres of origin of especially strong avalanches. The high snowiness of this territory, ascompared to neighbouring areas, is conditioned by the influence of the orography and the climate effect, that is seen on the map of the solid precipitation distribution in the Atlas of Snow and Ice Resources of the World (1997). Only in this sector of the Greater Caucasus is there a kind of “peninsula” of high snowfall extending for tens of kilometers towards the moisture-bearing airflows from the Black Sea. Temperature conditions in the zone of increased snow accumulation are the factor contributing to the avalanche formation, which is manifested in its structural, textural and strength properties.